Extracellular Matrix Mineralization Promotes E11/gp38 Glycoprotein Expression and Drives Osteocytic Differentiation - Prideaux, Matthew; Loveridge, Nigel; Pitsillides, Andrew A.; Farquharson, Colin (PLOS ONE, 2012)
Osteocytes are terminally differentiated osteoblasts which reside in a mineralized extracellular matrix (ECM). The factors that regulate this differentiation process are unknown. We have investigated whether ECM mineralization could promote osteocyte formation. To do this we have utilised MLO-A5 pre-osteocyte-like cells and western blotting and comparative RT-PCR to examine whether the expression of osteocyte-selective markers is elevated concurrently with the onset of ECM mineralization. Secondly, if mineralization of the ECM is indeed a driver of osteocyte formation, we reasoned that impairment of ECM mineralization would result in a reversible inhibition of osteocyte formation. Supplementation of MLO-A5 cell cultures with ascorbic acid and phosphate promoted progressive ECM mineralization as well as temporally associated increases in expression of the osteocyte-selective markers, E11/gp38 glycoprotein and sclerostin. Consistent with a primary role for ECM mineralization in osteocyte formation, we also found that inhibition of ECM mineralization, by omitting phosphate or adding sodium pyrophosphate, a recognized inhibitor of hydroxyapatite formation, resulted in a 15-fold decrease in mineral deposition that was closely accompanied by lower expression of E11 and other osteocyte markers such as Dmp1, Cd44 and Sost whilst expression of osteoblast markers Ocn and Col1a increased. To rule out the possibility that such restriction of ECM mineralization may produce an irreversible modification in osteoblast behaviour to limit E11 expression and osteocytogenesis, we also measured the capacity of MLO-A5 cells to re-enter the osteocyte differentiation programme. We found that the mineralisation process was re-initiated and closely allied to increased expression of E11 protein after re-administration of phosphate or omission of sodium pyrophosphate, indicating an ECM mineralization-induced restoration in osteocyte formation. These results emphasise the importance of cell-ECM interactions in regulating osteoblast behaviour and, more importantly, suggest that ECM mineralization exerts pivotal control during terminal osteoblast differentiation and acquisition of the osteocyte phenotype.